2005
DOI: 10.1002/cncr.20906
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ductal resection margin status on long‐term survival in patients undergoing resection for extrahepatic cholangiocarcinoma

Abstract: BACKGROUNDThe current study was performed to clarify whether the presence of residual carcinoma in situ at ductal resection margins differs prognostically from residual invasive ductal lesions in patients undergoing surgical resection for extrahepatic cholangiocarcinoma.METHODSA retrospective analysis of 84 patients with extrahepatic cholangiocarcinoma who underwent surgical resection was conducted. The ductal resection margin status was classified as negative (n = 64 patients), positive with carcinoma in situ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
217
2
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 215 publications
(226 citation statements)
references
References 24 publications
6
217
2
1
Order By: Relevance
“…26, 27, 28, 31, 32, 34, 35, 38 The reported incidences of complete resection with histopathologically negative margins ranged from 69% to 87% 26, 27, 28, 31, 32, 34, 35, 38. All the studies included in Table 1 confirmed that ductal resection margin status was an independent prognostic factor in patients with extrahepatic cholangiocarcinoma.…”
Section: Biological Behavior Of Residual Carcinoma In Situmentioning
confidence: 81%
See 4 more Smart Citations
“…26, 27, 28, 31, 32, 34, 35, 38 The reported incidences of complete resection with histopathologically negative margins ranged from 69% to 87% 26, 27, 28, 31, 32, 34, 35, 38. All the studies included in Table 1 confirmed that ductal resection margin status was an independent prognostic factor in patients with extrahepatic cholangiocarcinoma.…”
Section: Biological Behavior Of Residual Carcinoma In Situmentioning
confidence: 81%
“…Differentiation between severe dysplasia and carcinoma in situ may be difficult or impossible. Therefore, in several clinical studies,26, 27, 28, 35, 36, 38, 39 severe (high‐grade) dysplasia has been categorized as carcinoma in situ. Severe dysplastic epithelium or carcinoma in situ may extend into intramural glands such as the sacculi of Beale or metaplastic pyloric type glands 42.…”
Section: “Carcinoma In Situ”: Histopathological Terminologymentioning
confidence: 99%
See 3 more Smart Citations